Mutual antenna coupling influence on the channel correlation matrix for linear antenna arrays - Tatiana K. Artemova; Aleksey S. Gvozdarev; Konstantin S. Artemov (Institute of Advanced Engineering and Science, 2021)
The paper presents the results of the research of electromagnetic mutual coupling impact on the structure of the correlation matrices in multiantenna communication systems. Classical correlation structures employed in most of the up-to-date communication systems descriptions and designs usually assume unit autocorrelation and exponentially decreasing cross-correlation of antenna elements in the receiving/transmitting array. At the same time numerous studies had shown that these assumptions may not hold under certain conditions. The performed research relates the correlation effects with the imbalances of the array impedance matrix terms and studies the impact of antenna elements mutual electromagnetic interaction upon the diagonal (autocorrelation) and off-diagonal (cross-correlation) terms of correlation matrix, depending of the geometry of the array: number of elements and their spatial separation. To exemplify quantitative results the analysis was carried out for the 5G NR #78 band, being one of the most wideband subchannels in Under-6 GHz regime for 5G systems. The obtained results also justified the applicability of the banded correlation matrix model for wireless communications.